Mass Spectral Studies of Some 3-Benzyloxy Flavones - Ashawa, Anjana; B. Bhandari, Rani; L. Verma, Basant (Asian Journal of Chemistry, 2010)
Mass spectral fragmentation pattern of four 3-benzyloxy flavones has been discussed